2018
DOI: 10.1016/j.fertnstert.2018.04.012
|View full text |Cite
|
Sign up to set email alerts
|

Endometritis: new time, new concepts

Abstract: Endometritis is subdivided into two categories. Acute endometritis is symptomatic and characterized by microabscess formation and neutrophil invasion in the endometrial superficial epithelium, gland lumina, and uterine cavity. Chronic endometritis is rather silent and recognized as unusual plasmacyte infiltration in the endometrial stromal areas. Over the last decade, studies have disclosed the potential association between poor reproductive outcomes and endometritis, particularly chronic endometritis. The aim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
165
3
18

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 211 publications
(222 citation statements)
references
References 79 publications
6
165
3
18
Order By: Relevance
“…Chronic endometritis (CE), the best‐studied subclinical inflammation of the endometrial lining, is mainly caused by infection with common bacteria such as Enterobacteria, Streptococcus species, and Enterococcus faecalis , as well as Chlamydia , Mycoplasma , and Ureaplasma species, although yeast can be also involved, to the detriment of the protective LD microbiota . The reported prevalence of this disease in reproductive‐age women varies from 8% to 72%, and it is associated with repeated implantation failure and recurrent pregnancy loss . However, because it is often asymptomatic, it is rarely suspected, diagnosed, and treated.…”
Section: Role Of Bacteria In Women's Healthmentioning
confidence: 99%
See 1 more Smart Citation
“…Chronic endometritis (CE), the best‐studied subclinical inflammation of the endometrial lining, is mainly caused by infection with common bacteria such as Enterobacteria, Streptococcus species, and Enterococcus faecalis , as well as Chlamydia , Mycoplasma , and Ureaplasma species, although yeast can be also involved, to the detriment of the protective LD microbiota . The reported prevalence of this disease in reproductive‐age women varies from 8% to 72%, and it is associated with repeated implantation failure and recurrent pregnancy loss . However, because it is often asymptomatic, it is rarely suspected, diagnosed, and treated.…”
Section: Role Of Bacteria In Women's Healthmentioning
confidence: 99%
“…One of the challenges of CE management today is the lack of universally standard criteria for the diagnosis of the disease (ie, number of plasma cells identified per area of screened tissue sections). While the current gold‐standard method relies on histopathological identification of plasmacyte infiltrations in the endometrial stroma coupled to CD138 immunohistochemistry, other authors promote hysteroscopic examination of the uterine cavity or the classical culture of endometrial specimens . However, many confounding factors affect the assessment of CE: the method of analysis, the criteria used to discriminate positive and negative samples, the phase of the cycle in which the endometrium is evaluated (ie, the estimated prevalence of CE is approximately 50% higher in endometrial samples collected in the proliferative vs the secretory phase), or even the reagents used in the laboratory developing the test .…”
Section: Role Of Bacteria In Women's Healthmentioning
confidence: 99%
“…69,70 Moreover, recent studies have demonstrated that G-CSF treatment in women with recurrent IVF failure improved implantation and pregnancy rates. 83 Furthermore, use of these in vivo and in vitro models provides an avenue to identify and test targets for therapeutic intervention, ultimately improving fertility. 72,73 Primary human endometrial stromal cells decidualized in the presence of LPS expressed significantly lower transcript levels of decidual biomarkersIGFBP1 and PRL compared to those decidualized without LPS ( Figure 5A).…”
Section: Identifying the Molecular Changes That Accompany Lps-inducmentioning
confidence: 99%
“…As chronic endometritis is associated with poor reproductive outcomes, these new models are directly relevant to enhancing our understanding of how bacterial endotoxins alter the uterine environment. 83 Furthermore, use of these in vivo and in vitro models provides an avenue to identify and test targets for therapeutic intervention, ultimately improving fertility. 84…”
Section: Characterizing Cytokine and Chemokine Release In Primary Hmentioning
confidence: 99%
“…In recent years, with the development of high-throughput sequencing technology of 16S rDNA gene, which is possible to analyze the diversity of bacterial community in different ecological niches. Growing evidence suggests that the intestinal micro ora affects many important physiological functions of the host, such as immune system activation, metabolism, epithelial cell proliferation and anti-infection [4].…”
Section: Introductionmentioning
confidence: 99%